Student Error in Grade X on the Concept of Trigonometry Using a Hermeneutic Phenomenological Study - Syifa, Alifia Qolbiyatus; Kurniawati, Ira (Jurnal Pendidikan Matematika, 2025)
Trigonometric Comparison is an E-phase mathematics material of class X geometry elements in the Merdeka Curriculum. This study aims to identify students' difficulties and learning obstacles in understanding the material. This research employs a qualitative study design using a hermeneutic phenomenological approach, focusing on grade X students and their math teacher as subjects. Data were collected through written tests (TKR), documentation, and interviews. Then it was analyzed using Ricoeur's stages. The research sample was selected purposively based on the meaning category of students' answers to TKR questions, which were grouped into four categories. The results indicated that students had difficulty in choosing the right trigonometric ratio and understanding the context of applied problems. Furthermore, the findings reveal three categories of learning obstacles as proposed by Brousseau, which students encounter: ontogenic obstacles of a psychological nature, indicated by students' low interest and motivation in learning; instrumental obstacles, reflected in the imbalance between students' use of concept images and concept definitions; and conceptual obstacles, due to students' lack of mastery of prerequisite knowledge. In addition, epistemological obstacles were identified, as evidenced by students' difficulties in solving problems presented in various forms, and didactical obstacles, as demonstrated by the teachers' rapid and superficial delivery of the material. These findings suggest that students' learning obstacles are interconnected between internal factors (within the students) and external factors.